MINYAK NABATI SEBAGAI PENGGANTI BAHAN KIMIA TOKSIK PADA PROSES CLEARING JARINGAN HISTOPATOLOGI - Balqis Mezzaluna D'Azzuri; Susianti Susianti; Nisa Karima (CV. Jasa Sukses Abadi, 2023)
The clearing stage is an important step in preparing tissue histology to be examined under a light microscope, clearing is done to clean the tissue so that it is possible to insert it with an embedding material. Xylene is the material most widely used because of its excellent compatibility with fixing materials such as alcohol and paraffin. However, xylene is known to have various toxic effects on the exposed body. Many alternative materials have been found to replace xylene as a clearing agent in the process of making histopathological tissues. These ingredients are vegetable oils including coconut oil, peanut oil, olive oil, palm oil, and corn oil. These materials can be used as clearing agents without affecting the histological tissue composition, are more affordable, and do not cause health problems.